Nitrogen-enriched activated carbon derived from plant biomasses: a review on reaction mechanism and applications in wastewater treatment - Bumajdad, Ali; Khan, Mohammad Jakir Hossain; Lukaszewicz, Jerzy P. (Frontiers in Materials, 2023)
As a key kind of evolving carbonaceous adsorbent, nitrogen-enriched activated carbon has drawn a lot of focus due to its better physiochemical ability to eliminate an extensive range of wastewaters contaminants under severe conditions. Its environment-friendly character is one more reason behind this focus. Nitrogen also has immense effect on activated carbon structures’ pollutants adsorption capability; therefore, it is an area of interest. Reports concerning the reaction pathway of C-N (carbon-nitrogen) bond creation on AC surface are limited. Determining such mechanisms is challenging but critical to understand bond characteristics after carbonization. Moreover, it is vital to ascertain real-time kinetics concerning adsorption phenomena in liquid phase. Such a latest trend indicates that regulated nitrogen uses for carbonaceous substances having a biomass-based origin can provide the desired morphological characteristics produced through interconnections, production of enclosed holes, enhanced surface area, better adsorption ability, and many other benefits in contrast to conventional carbon-based substances. This review points out the developments in the main processes to introduce nitrogen atoms into the carbon matrix by utilizing different N-comprising chemical compounds. The nitrogen enrichment processes, reaction mechanisms and effects of nitrogen incorporation on the plant biomass-derived activated carbons (NEACs) are presented in brief. On the basis of their established physicochemical attributes, the adsorption performances of different biomass-derived NEACs have also been dealt with. More significantly, the review covers the technical issues in the present phase, topical trends, research gaps, economic viability along with a technical alignment recommendation to address the prevailing disadvantages.